RELATIVITY INDEX OF THE RELIABILITY OF SPACE SYSTEMS - Petrov, Nikolay (International Journal of Computing, 2011)
According to the special theory of relativity by Einstein, it can be affirmed that two events coincide in space only when objects are shown (or system of objects); according to latter the position of these events is defining. In this way the term “position in space” is relative too. When we talk about the position of one object in space – it’s actually its position among other objects. However, if we have to give answer to the question “where is the current object?” without mentioning about the condition of adjacent objects, it follows that this question will be meaningless. In this article has been done a trial for taking of theoretical dependence, which defines the probability for no-failure of mobile space systems (spacecraft), moving with determinate speed towards an observer on the Earth.